IMPLEMENTING AUTHENTIC MATERIALS OF PROCEDURE TEXTS TO FOSTER STUDENTS’ SPEAKING ACHIEVEMENT AT THE SECOND GRADE OF SENIOR HIGH SCHOOL - Alexander Bastian, Arif (Aisyah Journal of English Language Teaching (AIJELT), 2022)
The purpose of this study was to examine second-year high school students' attitudes toward the use of authentic materials in the classroom and to determine whether or not they had a positive impact on their speaking performance when reading procedural texts. Thirty students from Science 3 class at SMA N 15 in Bandar Lampung were selected as the sample for this study. In this study, participants were divided into a pre- and post-test group. The questionnaire and oral communication test were used to compile the data. According to the findings, students' proficiency in public speaking was elevated after being exposed to authentic materials. The average gain was 17.40 points, with post-test scores averaging 79.43 compared to the pre-test average of 62.03. A p-value of 0.05 or less indicates that the level of significance is lower than the data. Using primary sources may have helped students improve their public speaking skills. Contrarily, 22 students (73.03%) reported being active, liking, and satisfied with the teaching learning process when using authentic materials. The preceding findings suggest that using genuine resources can boost students' speaking proficiency in procedure texts and increase their satisfaction with the classroom experience.